Contextual Priming and the Design of 3D Virtual Environments to Improve Group Ideation - Bhagwatwar, Akshay; Massey, Anne; Dennis, Alan (Information Systems Research, 2018)
Three-dimensional (3D) virtual environments (VEs) are collaboration platforms where group members are represented as avatars and interact in a customizable simulated world. Research from cognitive psychology has shown that it is possible to manipulate nonconscious cognition and behavior through “priming,” a well-known phenomenon in which words and images are used to activate desired concepts in participants’ minds. Our goal in this was to investigate whether priming during the task execution (called contextual priming) using 3D objects in the VE can improve brainstorming performance. To investigate this, we conducted two studies. The first used priming objects specifically related to the task topic and the second used priming objects related to creativity, in general. Compared to VEs without 3D priming objects, our results show that when groups brainstormed in the VEs designed with 3D priming objects, they generated better quality ideas as well as a greater breadth and depth of ideas. Thus, the 3D priming stimuli incorporated in a VE enhances brainstorming, which indicates that the design of VE has a direct effect on team brainstorming performance. Our results also show that target concept activation and task absorption act as the underlying mechanisms, partially mediating the relationship between the design of the VE (i.e., the presence or absence of priming objects) and performance outcomes.